Accessory Anteromedial Portal may not Provide Clinically Superior Results Compared with the Anteromedial Portal in Anterior Cruciate Ligament Reconstruction - Ye, Shu-Ming; Jing, Jue-Hua; Lv, Hao; Zhang, Ji-Sen; Xu, Xin-Zhong; Xu, Chun-Gui; Zhou, Yun; Xu, You-Jia (The Journal of Knee Surgery, 2018)
Techniques using the anteromedial portal (AMP) and accessory anteromedial portal (AAMP) are commonly used in anterior cruciate ligament (ACL) reconstruction. The aim of this study was to investigate the radiological and clinical outcomes of arthroscopic single-bundle ACL reconstruction using the AMP or AAMP technique to drill the femoral tunnel. The records of 157 patients who underwent single-bundle ACL reconstruction using the AMP or AAMP technique between 2011 and 2015 were reviewed. The femoral tunnel clock-face position and femoral tunnel and tibial tunnel anterior–posterior (AP) inclination angles were assessed on axial or AP magnetic resonance images. At last follow-up, the Lachman test and pivot-shift test were used to evaluate AP and rotational stability, respectively. The Lysholm knee scoring scale and the International Knee Documentation Committee (IKDC) form were used to evaluate clinical and functional results. No statistically significant differences were found between the groups in patient age, sex, follow-up period, or affected side distribution. The mean femoral tunnel inclination angle was 31.13 ± 8.06 degrees in the AMP group and 30.17 ± 9.02 degrees in the AAMP group (p = 0.513). The tibial tunnel inclination angle in the AMP group (16.28 ± 7.89 degrees) was not different from that in the AAMP group (13.70 ± 6.08 degrees). No significant differences were observed between the two groups in the Lachman test, pivot-shift test, Lysholm knee scoring scale, or IKDC scores. The AAMP technique was not clinically superior to the AMP technique in ACL reconstruction. This is a retrospective comparative study and its level of evidence is III.
Keywords: anterior cruciate ligament; reconstruction; knee; femoral tunnel; anteromedial portal